Relationship between change of direction, speed, and power in male and female National Olympic Team handball athletes - Pereira, L. A.; Nimphius, S.; Kobal, R.; Kitamura, K.; Turisco, L. A. L.; Orsi, R. C.; Cal Abad, C. C.; Loturco, I. (The Journal of Strength and Conditioning Research, 2018)
The aims of this study were to (a) assess the relationship between selected speed- and power-related abilities (determined by 20-m sprint, unloaded countermovement jump [CMJ] and squat jump [SJ], and loaded jump squat [JS]) and performance in 2 distinct change of direction (COD) protocols (Zigzag test and T-test) and (b) determine the magnitude of difference between female and male Brazilian National Olympic Team handball athletes. Fifteen male and 23 female elite handball athletes volunteered to perform the following assessments: SJ and CMJ; Zigzag test and T-test; 20-m sprint with 5-, 10-, and 20-m splits; and mean propulsive power in JS. Pearson's product-moment correlation (p = 0.05) was performed to determine the relationship between the COD tests (Zigzag test and T-test) and speed-power measures (sprint, SJ, CMJ, and JS). The differences between male and female performances were determined using the magnitude-based inference. Moderate to very large significant correlations were observed between both COD tests and the speed-power abilities. Furthermore, male athletes demonstrated likely to almost certainly higher performances than female athletes in all assessed variables. The results of the current study suggest that different speed-power qualities are strongly correlated to the performance obtained in various COD assessments (r values varying from 0.38 to 0.84 and from 0.34 to 0.84 for correlations between speed and power tests with Zigzag test and T-test, respectively). However, the level of these associations can vary greatly, according to the mechanical demands of each respective COD task. Although COD tests may be difficult to implement during competitive seasons, because of the strong correlations presented herein, the regular use of vertical jump tests with these athletes seems to be an effective and applied alternative. Furthermore, it might be inferred that the proper development of loaded and unloaded jump abilities has potential for improving the physical qualities related to COD performance in handball athletes.